Interaction between dark matter sub-halos and a galactic gaseous disk - Kannan, Rahul; Pasquali, Anna (The astrophysical journal, 2012)
We investigate the idea that the interaction of dark matter (DM) sub-halos with the gaseous disks of galaxies can be the origin for the observed holes and shells found in their neutral hydrogen (H I ) distributions. We use high-resolution hydrodynamic simulations to show that pure DM sub-halos impacting a galactic disk are not able to produce holes; on the contrary, they result in high-density regions in the disk. However, sub-halos containing a small amount of gas (a few percent of the total DM mass of the sub-halo) are able to displace the gas in the disk and form holes and shells. The sizes and lifetimes of these holes depend on the sub-halo gas mass, density, and impact velocity. A DM sub-halo, of mass 10 8 M ☉ and a gas mass fraction of 3%, is able to create a kiloparsec-scale hole with a lifetime similar to those observed in nearby galaxies. We also register an increase in the star formation rate at the rim of the hole, again in agreement with observations. Even though the properties of these simulated structures resemble those found in observations, we find that the number of predicted holes (based on mass and orbital distributions of DM halos derived from cosmological N -body simulations) falls short compared to the observations. Only a handful of holes are produced per gigayear. This leads us to conclude that DM halo impact is not the major channel through which these holes are formed.